Variation in the serum proteins of the red-backed mice Clethrionomys rutilus and C . gapperi and its taxonomic significance - Canham, Raymond P.; Cameron, David G. (Canadian Journal of Zoology, 1972)
Starch gel electrophoresis revealed the existence of four transferrins, five albumins, and 17 α-globulins in the serum of red-backed mice from nine locations in western Canada. Two of the transferrins and one of the albumins occurred in populations of both Clethrionomys rutilus and C. gapperi, but every population sampled contained at least one of the remainder of these proteins at a moderately high frequency. Populations of the two species near the boundary between their ranges of distribution could also be distinguished by the frequencies of the shared transferrins and albumins. Eight of the α-globulins were found only in C. gapperi, and two only in C. rutilus. Populations of the two species could not invariably be distinguished by means of these proteins: the same seven α-globulins were present in both species near their common boundary in the Northwest Territories, although only one was shared by populations on either side of the boundary in the Rocky Mountains of British Columbia. Several α-globulins were found only in samples of C. gapperi from southern Alberta. Differences between populations with respect to the α-globulins present, as well as to the frequencies of certain transferrins and α-globulins, were probably the result of differences in the environmental conditions to which the populations were subject.